2016
DOI: 10.1177/155892501601100307
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Preparation of the AOPAN/MMT Composite Nanofibers and Their Application for Laccase Immobilization

Abstract: In this paper, a novel nano-material was prepared, and then was applied for enzyme immobilization. Amidoxime ployarcylonitrile /montmorillonite (AOPAN/MMT) composite nanofibrous membranes were generated by electrospinning and amidoxime modification, then the nanofiber membranes were modified by glutaraldehyde; the modified AOPAN/MMT composite nanofibers were applied in laccase immobilization by adsorption and crosslinking method. Scanning electron microscopy was used to visualize the morphology of the nanofibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Also, Jiang et al immobilized laccase onto chitosan microspheres and observed 70% of activity retention after one month storage at 4±1 °C, while free enzyme resulted in 30% of its initial activity [27]. and laccase and therefore lost only 30% of laccase activity after 7 cycles of ABTS oxidation [29]. Likewise, Xu et al immobilized laccase onto PAN nanofibers through amidination process and reported that the immobilized laccase lost 30 % of the initial activity after 7 cycles [25].…”
Section: -9-immobilization Of Laccase Onto Pan-biochar Membranementioning
confidence: 99%
“…Also, Jiang et al immobilized laccase onto chitosan microspheres and observed 70% of activity retention after one month storage at 4±1 °C, while free enzyme resulted in 30% of its initial activity [27]. and laccase and therefore lost only 30% of laccase activity after 7 cycles of ABTS oxidation [29]. Likewise, Xu et al immobilized laccase onto PAN nanofibers through amidination process and reported that the immobilized laccase lost 30 % of the initial activity after 7 cycles [25].…”
Section: -9-immobilization Of Laccase Onto Pan-biochar Membranementioning
confidence: 99%
“…reported a slight improvement in thermal stability of immobilized laccase (20-45%)21,25 , Jiang et al observed higher sensitivity of laccase after immobilization onto chitosan compared to free laccase (up to 65 %)14 .…”
mentioning
confidence: 98%
“…[42] Thus, it is possible to see the influence of the concentration of glutaraldehyde as a parameter for laccase immobilization. This was reported by Feng et al (2016) when they covalently immobilized the laccase on amidoxime polyacrylonitrile/montmorillonite (AOPAN/ MMT) nanofibrous membrane. The researchers noticed that the increase in the concentration of glutaraldehyde provided an increase in the amount of immobilized laccase until reaching a saturation point of 5 %, where the amount of laccase reached 89.12 mg/g, maximum retention of enzyme in the support.…”
Section: R E C O R D R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 67%
“…The researchers noticed that the increase in the concentration of glutaraldehyde provided an increase in the amount of immobilized laccase until reaching a saturation point of 5 %, where the amount of laccase reached 89.12 mg/g, maximum retention of enzyme in the support. [43] Another method used is the activation of the PAN surface by amidination (Figure 2b), where the nitrile groups of polyacrylonitrile are activated in a medium containing ethanol/ HCl resulting in the production of imidoester, which in turn reacts with the amino groups present in the enzyme to form amidino bonds. [44] The laccase was immobilized on amidina-tion activated nanofiber PAN and successfully applied to remove 2,4,6-trichlorophenol (TCP) from the water.…”
Section: R E C O R D R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%